MicroRNAs in Hepatocellular Carcinoma: Regulation, Function, and Clinical Implications - Jie Sun; Haiqi Lu; Xian Wang; Hongchuan Jin (The Scientific World Journal)
Hepatocellular carcinoma (HCC) is one of the most common cancers worldwide and the third cause of cancer-related death. Poor understanding of the mechanisms underlying the pathogenesis of HCC makes it difficult to be diagnosed and treated at early stage. MicroRNAs (miRNAs), a class of noncoding single-stranded RNAs of ~22 nucleotides in length, posttranscriptionally regulate gene expression by base pairing with the 3′ untranslated regions (3′UTRs) of target messenger RNAs (mRNAs). Aberrant expression of miRNAs is found in many if not all cancers, and many deregulated miRNAs have been proved to play crucial roles in the initiation and progression of cancers by regulating the expression of various oncogenes or tumor suppressor genes. In this Paper, we will summarize the regulations and functions of miRNAs aberrantly expressed in HCC and discuss the potential application of miRNAs as diagnostic and prognostic biomarkers of HCC and their potential roles in the intervention of HCC.